Tracing the Past, Uncovering the Present: Intergenerational Hauntings among Cambodian-Australian Women. (1st November 2020) - Hach, Maria
ABSTRACT: This paper explores the affective force of the Cambodian genocide among Cambodian-Australian women. It draws on Lily Cho and Avtar Brah's understanding of diasporas as communities that are connected to histories of loss, grief and displacements (Cho [2007]. The Turn to Diaspora. Topia, 17, 11–30) and embodying a 'homing desire' (Brah 1996) and Avery Gordon's ([2008]. Ghostly Matters: Haunting and the Sociological Imagination . Minneapolis: University of Minnesota Press.) theory of 'haunting' to explore the traces of historical trauma. Through anaccount of a Cambodian-Australian woman living in Cambodia, this paper demonstrates that intergenerational hauntings can provoke affective states that are embodied, encompassing emotions such as sadness, guilt, pain, and joy, tied to longings and connections with one's history and heritage. Certainly, embodied hauntings reflect histories of grief and loss, and yet from this loss, something else, something beyond psychopathology emerges. Highlighting the generative possibilities of affect, this paper examines how intergenerational hauntings can open up new ways of thinking about identity and agency. As illustrated by Sanna's story, hauntings can be expressed by a desire to actively engage with the past, recover histories and 'return' to Cambodia. In particular, this paper explores how trauma is experienced and embodied from mother to daughter, highlighting the gendered nature of intergenerational hauntings.